Room-temperature NH3 gas sensors based on heterostructures PbS/CdS - S. L. Prokopenko; G. M. Gunja; S. M. Makhno; P. P. Gorbyk (Хімія, фізика та технологія поверхні)
In order to develop sensors capable to detect harmful gases at the ambient temperature, the semiconductor heterostructure PbS/CdS has been synthesized. Formation of CdS nanorods was conducted in the presence of ethylenediamine. An ion-exchange method was used to deposit PbS nanoparticles over the CdS nanorods to produce a large area of the surface heterojunction. Series of samples of with variation in the PbS amount on the CdS surface (from 2.5 to 20mol.%) was obtained. Surface morphology, optical properties and performance characteristics of the PbS/CdS heterostructure gas sensors were studied. The sample performance characteristics were measured by means of change in electric resistance of sensor due to reaction between the surface of material and NH3 in saturated vapours of ammonia. The gas sensor based on the PbS/CdS heterostructures have shorter response and recovery time compared to a sensor based on the CdS solely. It has been shown that with increase in amount of PbS on the CdS surface from 2.5 to 20mol.% the sensor response rate becomes 1.7 times greater.